The mapping of salinity level using the Inverse Distance Weighted (IDW) interpolation method along the coastal area of Pulau Tuba, Langkawi / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Abd.Aziz, Khairul Naim; Roslani, Muhammad Akmal; Zainol, Zamzila Erdawati; Ahmad, Aziani; Shaari, Mohd Idrus; Nazri, Rosnani; Tajam, Jamil (Universiti Teknologi MARA, Perak, 2022)
The purpose of this study is to investigate the accuracy of the Inverse Distance Weighted (IDW) interpolation method to estimate and map the surface water salinity along the coastal waters of Pulau Tuba, Langkawi. Sea surface salinity was recorded using a refractometer during two sampling activities that were carried out in November 2018. The Global Positioning System (GPS) was used to record the geo-location of each sampling point. IDW method was applied in data collection using ArcGIS Software. Statistical analyses such as correlation analysis, regression analysis, and error analysis were employed to assess the prediction of salinity values. The transformation of the spatial model to map was carried out later to assess the accuracy of the map. The study found that there is a strong positive correlation, r= .753 (p< .05) with the coefficient of determination of 56.80% between observed and predicted salinity values. Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) were calculated at 0.724466 and 0.921728, respectively. The accuracy of the map was found at 81.25%. The study also found that the salinity reading is polyhaline along the coastal water of Pulau Tuba. Overall, the study found that the IDW method has provided a tool to predict and map the surface salinity along the coastal waters of Pulau Tuba, Langkawi.